Impactos da pandemia de COVID-19 no comportamento de consumo de produtos lácteos: mudanças nos hábitos de consumidores brasileiros - Souza, Laura de Paula (2022)
The COVID-19 pandemic caused several changes in the daily life of the world population that affected the purchase and consumption of food. There was even an increase in factors such as stress, anxiety, fear and uncertainty, which directly impact eating habits. However, little is known about the influence of these factor on the consumption of dairy products, especially those with high sensory appeal and that can help maintain health and the immune system. Therefore, the present study aims to map changes in the frequency of consumption of dairy products, analyze changes in purchase habits and its drivers, as well as verify the influence of perception of risk and stress on consumption during the most critical period of the pandemic (between March 2020 and August 2021) in Brazil. For this, a descriptive study with a quantitative nature was carried out with brazilian consumers through an online questionnaire, with non-probabilistic sampling and 376 respondents. The questionnaire was structured in 5 sections, totaling 24 objective questions. The collected data were processed using SPSS software, v. 20, and submitted to cluster analysis, chi-square test and Kruskal-Wallis test. Through the studies carried out, it is concluded that there was a change in the frequency of consumption of dairy products in general, although most consumers indicate that it remained the same as before the pandemic. The perception of risk to COVID-19 had little influence on the consumption of dairy products in general and with an appeal to healthiness, as well as the importance given to various purchase drivers. The perception of stress was significantly associated with the frequency of consumption of dairy products with sensory appeal: individuals with high stress significantly increased the consumption of indulgent dairy products. In addition, a high level of stress was also significantly associated with an increase in the importance given to purchase drivers associated with mood and price, such as: “helps me to cope with stress”, “helps me to relax”, and “is cheap". As for shopping habits, most of the interviewees stated that they had kept the same frequency of buying dairy products in supermarkets, bakeries and grocery stores in the neighborhood. On the other hand, delivery/app purchases, especially pizza and sandwiches, had a significant increase. In addition, there was also an increase in the purchase of dairy products for the production of homemade recipes in relation to the pre-pandemic period.